Study on groundwater recharge assessment by rainfall in coastal district Thai Thuy, Thai Binh province - Nguyen Van, Hoang; Pham Lan , Hoa; Dong Thu , Van; Le Quang, Dao (Vietnam Journal of Marine Science and Technology, 2021)
Groundwater always plays a vital role in socio-economic development. One of the components of groundwater resource potential is the recharge from rainfall and surface water. The paper presents finite element modeling in the moisture transfer simulation in unsaturated soils through the relationship between soil moisture, soil suction, unsaturated permeability, and moisture dispersion coefficient. Parameters required for moisture transfer in four subsurface soil types have been collected and analyzed: Saturated permeability, porosity and field moisture content. Hourly rainfall data of 2015 have been studied and grouped into different rainfall duration (1-hour, 2-hour,... 36-hour continuous rainfall). The different duration rainfall and temporal infiltration determined by the moisture transfer modeling allow calculating the groundwater recharge from the downpour. We had applied the methodology to coastal district Thai Thuy, Thai Binh province. The results show that during the rainy months from June to October 2015, the groundwater recharge from the rainfall is: Through silty clay 0.233 m, through silt 0.338 m, through sandy silt 0.374 and through silty sands 0.561 m. The rainfall recharge to groundwater through those four soil types in terms of percentage of total 2015 rainfall respectively is 12.85%, 18.65%, 20.63% and 30.95%. The methodology may be applied to other areas with an advantage in the minimal expense of budget and time and relatively high reliable results.